The effects of geometrical configuration onto measuring ensemble averaged surface Normal impedance - Che Din, Nazli; Otsuru, Toru; Tomiku, Reiji; Okamoto, Noriko (2011)

(untitled)
An in situ measurement technique of a material’s surface impedance using ambient noise was proposed by some of the authors to offer the utilization in actual environment mainly in architectural acoustics. Furthermore, in the previous paper the theoretical development and concept of “Ensemble Averaged” surface normal impedance were summarized using the math-physical model based on the boundary element method (BEM) by the authors. This paper further elaborates on past discussions on the ensemble averaged surface normal impedance method of measuring surface impedance and the absorption coefficient of materials. In investigating the level of utility in various applications, the effects of source-receiver-sample geometrical configuration are presented both in simulation and measurement. Several measurements are conducted in two experimental rooms, i.e. reverberation room and anechoic room. The resulting absorption characteristics are examined to propose an appropriate measurement setting and demonstrate the accuracy and general utility of the method. Through the investigation, the applicability, reliability and robustness of the proposed method are revealed.